Agriculture Subsidies for Better Outcomes : Options For Zimbabwe - World Bank (World Bank, Washington, DC, 2020)
Zimbabwe has a long history of providing subsidies to farmers. The policies that have defined these subsidies have changed over time and led periodically to significant and unsustainable pressure on fiscal resources. Agricultural subsidy costs are a main driver of recent fiscal imbalances and inflationary pressure. The Ministry of Finance and Economic Development is making efforts to bring them under control while maintaining adequate support to the agricultural sector during a significant drought and other structural challenges. This report contributes to the identification and scoping of options for redesigning agricultural subsidies in Zimbabwe so that their objectives, a mix of national food security, smallholder access to production technology, and trade balance strengthening can be pursued at significantly reduced fiscal costs. The first part of the report reviews informative cross-country surveys of agricultural subsidy programs (mostly for inputs) over the past decade. The second part briefly traces the phase-by-phase evolution of Zimbabwe’s agricultural subsidy policies. The third section reviews the cost of agricultural subsidies. The fourth section summarizes preliminary quantitative analysis of the impacts of Command Agriculture, inclusive of subsidies on maize yields. The last section introduces options and recommendations for bringing subsidy costs under control while maintaining broad-based support for farmer productivity and agricultural sector development.